GENESIS OF EXTREMELY MAGNESIAN DAUGHTER OLIVINE OF SECONDARY MELT INCLUSIONS FROM OLIVINE MACROCRYSTS IN KIMBERLITE FROM THE UDACHNAYA-EAST PIPE (SIBERIAN CRATON) - A. A. Tarasov; A. V. Golovin (Геодинамика и тектонофизика, 2024)
The paper presents the results of studies of daughter olivine within secondary melt inclusions marking healed cracks in olivine macrocrysts from unserpentinized kimberlite from the Udachnaya-East pipe. Macrocrysts compose four olivine generations: core olivine (Ol1); olivine marking healed cracks (Ol2); daughter olivine of melt inclusions (Ol3); thin outer rims of olivine (Olr) around macrocryst cores. The relationship between different olivine generations and variations in its chemical composition indicate that macrocrystal cores (Ol1) are grains or grain fragments of disintegrated mantle rocks; melt inclusions and Ol2 were formed due to infiltration of kimberlite melts into the grain cracks. Crystallization of a hybrid melt of inclusions and formation of an extremely magnesian daughter olivine (Ol3) occurred later, at lower PT conditions. Among the daughter minerals in the melt inclusions, in addition to Ol3 there were identified alkaline carbonates, sulfates, chlorides, oxides, and sulfides. It has been shown that the daughter olivine of melt inclusions (Ol3) has high Mg# (97–98) content, high MnO (0.18–0.41 wt. %) and CaO (0.12–0.25 wt. %) concentrations, and low NiO (0.02–0.04 wt. %) contents. The ratios between the daughter minerals of the melt inclusions indicate that the hybrid melt from which extremely magnesian olivine was formed was alkaline carbonate or silicate-carbonate liquid with a low water content. Our study directly showed for the first time that almost pure forsterite is able to be crystallized from evolved kimberlite melts of carbonate or silicate-carbonate composition, which confirms the previously proposed model for the formation of extremely magnesian outer rims of olivine crystals from worldwide kimberlites during crystallization of evolved kimberlite melts of carbonate composition.